Perbandingan Keabsahan Jual Beli Tanah Menggunakan Nominee dan Metode Tradisional: Tinjauan dari Hukum Positif - Antonia Wibawa; Joko Santono (SIMPUL: Jurnal Ilmu Politik dan Hukum, 2026)
Land sale and purchase agreements using a nominee or “borrowed name” system are often used to circumvent applicable legal restrictions, particularly those related to land ownership by foreign nationals. However, this practice has sparked debate regarding its validity under Indonesian positive law. This study aims to compare the validity of land sale and purchase agreements using nominees versus traditional methods, as well as to assess the legal implications arising from both practices. Using a legal-normative approach, this study analyzes relevant legislation, including the Basic Agrarian Law (UUPA) and regulations concerning land ownership by foreigners. The results indicate that while land sale and purchase agreements using nominees do not fully comply with existing legal provisions, this practice remains widely used in land transactions. Conversely, the traditional method, which follows proper legal procedures, tends to be more legally valid and provides stronger legal protection for the parties involved. This study concludes that the use of nominees in land sales carries the risk of legal disputes, whereas the traditional method is safer, although it is sometimes hindered by strict regulations.